Determination of the Optimum Stiffness Ratio to Achieve Optimal Blasting Fragmentation - Muhamad Athoriqi; Eko Santoso; Annisa Annisa; Muhammad Fajerin Dinata; Satrio Ramadhan (Universitas Lambung Mangkurat, 2026)
PT Adaro Indonesia operates in the coal mining industry, where overburden stripping is a critical stage of the production process. In several areas, this activity is carried out using drilling and blasting methods. The success of blasting operations can be evaluated through indicators such as the achievement of production targets, explosive efficiency, the quality of rock fragmentation, and potential environmental impacts. Optimal fragmentation is essential because it directly affects the efficiency of subsequent loading and hauling operations. One important parameter influencing fragmentation quality is the stiffness ratio used in blasting design. According to Decree of the Minister of Energy and Mineral Resources No. 1827 of 2018, the stiffness ratio is defined as the ratio between blast hole depth and burden distance. Theoretically, higher stiffness ratio values tend to produce better fragmentation. This study was conducted in the operational area of PT Adaro Indonesia by measuring actual blasting geometries in the field, with observations carried out on six blasting events. The results show that stiffness ratio values of 0.90, 0.98, 1.05, 1.18, and 1.21 produced rock fragmentation exceeding 85%. Among these, stiffness ratios of 1.21 and 1.18 generated the most optimal fragmentation performance. These findings highlight the importance of proper stiffness ratio design to improve blasting effectiveness and operational efficiency.